Simulation of Rapid Intensification of Super Typhoon Lekima (2019). Part II: The Critical Role of Cloud-Radiation Interaction of Asymmetric Convection - Huang, Qijun; Ge, Xuyang; Bi, Mingyu (Frontiers in Earth Science, 2022)
In this study, Super typhoon Lekima (2019) with an atypical rapid intensification (RI) episode is investigated by conducting a pair of experiments. In the control experiment, the model reproduces reasonably well the evolution characteristics of convective activity and intensity changes. That is, active downshear-left convection moved counterclockwise to the upshear flank. In the sensitivity experiment without the cloud-radiation feedback (CRF), the simulation fails to capture the observed upshear deep convection and the RI process. Our analyses suggest that the cloud-radiation interaction acts as positive feedback between the tilting-induced convective asymmetry (TCA) and outflow channel. On one hand, the radiative process will induce upper (lower) cooling (warming) above (within) the cloud anvil of the outflow layer. This thermodynamical pattern locally destabilizes the upper troposphere, and is conducive to enhance the deep convection. On the other hand, the enhanced deep convection provides the energy source to promote the upper divergent flows. The stronger divergent flow acts efficiently to block the vertical wind shear (VWS) and leads to a stronger outflow channel. This CRF assists in the development of a thicker and more radially extensive outflow than that CRF-off simulation. This study further confirms the outflow blocking effect, which gains the insights on the evolution of upshear-left asymmetric convection and its role in the atypical RI event.